Macrofungi Diversity in Mount Pandan Ectourism Area, Aceh Tamiang - Juli Trianda Sri Rejeki (Talenta Publisher, 2022)
Macrofungi are fungi that can be seen with the naked eye. Its characteristics can be seen based on its structure and body shape. Generally, fungi live in various types of habitats, namely wood, soil, litter, animal waste and so on. This research was conducted on 8-9 June 2022 in the Ecotourism area of Gunung Pandan, Aceh Tamiang Regency, Aceh Province. Determining the sampling point was carried out by the path method by observing macroscopic fungi along the hiking trail at a distance of 10 meters to the right and 10 meters. The most numerous macroscopic fungi, living solitary and these fungi were found in the Basidiomycota division, with 11 species and the least in the Thallophyta division, Eumycetes class, with 1 species.